TRADISI DI TENGAH KEBERAGAMAAN MEDIA INTERAKSI MASYARAKAT ENDE DALAM MEMBANGUN RELASI ANTARUMAT BERAGAMA (Harmoni, 2016)
Ende society are well known as a harmonious society regardless of the diverse identity and cultural character in language, ethnic groups and religion they have. It is also the case in the social structure of the society where we can find the number of religious adherents namely Catholics as the majority and Muslims as the minority. In fact, actually this region really has two potentials for inter-religious conflict to happen.  The question is, how is the role of local tradition in this diverse society? By applying sociological qualitative research through interviews, observations and documents collections, this research found that local knowledge in its various forms such as a way of life, a system of culture, the tradition of marriage, social institutions; has become an effective tool medium in keeping social relations among religions in Ende. Especially when all the elements of the ΓÇ£three stonesΓÇ¥ takes part in building social harmony in many factors like infrastructure development, education, community empowerment and so on. The social harmony between religious groups in Ende is getting stable because of the power of the value of local tradition.
Keywords: three stones (tiga batu tungku); interreligious relationship; Ende community; interaction media; Religious Tradition; Membangun Relasi.; Masyarakat Ende; Media Interaksi; Tradisi Keberagamaan